THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON STUDENTS' CRITICAL THINKING SKILLS IN ECONOMICS CLASS XI SMA - Suci Rahmadani; Friyatmi Friyatmi (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2025)
This study aims to determine the effect of problem-based learning model (X1) on students' critical thinking skills in economics class XI SMA at SMAN 1 Linggo Sari Baganti. This research is an experimental research with posttest only control group design. The population in this study were all grade XI students at SMAN 1 Linggo Sari Baganti. The sample in this study consisted of 1 control class and 1 experimental class. Data collection techniques in the form of critical thinking skills posttest. Instrument validation was carried out by expert validators, namely lecturers of the Department of Economic Education, Faculty of Economics and Business, Padang State University. The results of data analysis showed that the problem-based learning model had a significant effect on students' critical thinking skills in economics class XI SMA at SMAN 1 Linggo Sari Baganti.